Strengthening Last-Mile Capacity in Ethiopia: Climate Education for Resilience - Belay, Berhanu (International Livestock Research Institute, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025